2019
DOI: 10.1186/s12884-019-2400-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age and the risk of adverse pregnancy outcomes: a retrospective cohort study

Abstract: Background The increased potential for negative pregnancy outcomes in both extremes of reproductive age is a well-debated argument. The aim of this study was to analyze the prevalence and the outcome of pregnancies conceived at extreme maternal ages. Methods This retrospective study considered all single consecutive pregnancies delivered in a tertiary referral center between 2001 and 2014. Patients were categorized into 4 groups according to maternal age at delivery (< … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
140
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(178 citation statements)
references
References 53 publications
27
140
2
9
Order By: Relevance
“…But no research provided the threshold maternal age on BW was 34 years old [12,20,21]. We observed a marginal signi cantly negative association between maternal age and birth weight when maternal age ranged from35 to 40years, which was consistent with the ndings of the previous studies [22,23].…”
Section: Discussionsupporting
confidence: 91%
“…But no research provided the threshold maternal age on BW was 34 years old [12,20,21]. We observed a marginal signi cantly negative association between maternal age and birth weight when maternal age ranged from35 to 40years, which was consistent with the ndings of the previous studies [22,23].…”
Section: Discussionsupporting
confidence: 91%
“…A number of factors before and during pregnancy may affect the events of APO, including maternal age [20], smoking, excessive drinking [21,22], overweight or obesity, metabolic disorders (such as diabetes) [23,24], and some chronic diseases such as chronic kidney disease [25], systemic lupus erythematosus [26], cardiovascular diseases [27], and so on. The results indicated that pregnant women with APO were characterized by higher Hcy, TC, TG, LDL-C, FPG, age, SBP, DBP, and BMI, and lower folate, VB12, and HDL-C concentrations, compared with controls (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the association between maternal age and preterm birth; both extreme ages either under 18 years or above 40 years are considered to be risk factors for preterm birth 26 , 27 , 28 , 29 . Though the majority of the studies concluded that the older maternal age was associated with higher risk of preterm birth, Ambrogio and colleagues in their study observed that both extreme ages that is, maternal age under 17 and advanced age over 40 were independent factors for preterm birth (OR 2.97; 95%CI 1.24, 7.14 , P<0.005) 26 . This was echoed by Florent and co-authors who also found that both advanced age and lower age were risk factors for preterm birth 28 .…”
Section: Discussionmentioning
confidence: 93%